Classification of seismic activity at the Lazufre Volcanic System, based on 2011 to 2012 data - McFarlin, Heather; Thompson, Glenn; McNutt, Stephen R.; Braunmiller, Jochen; West, Michael E. (Frontiers in Earth Science, 2022)
The Lazufre Volcanic System (LVS), on the border of northern Chile and Argentina, is an active complex of two volcanoes, Lastarria to the north and Cordón del Azufre to the south. This system has shown unusual inflation signatures observed in InSAR and was recently classified as a top ten volcanic hazard in northern Argentina by the Observatorio Argentino de Vigilancia Volcánica of the Servicio Geológico y Minero Argentino. The LVS is not monitored by a permanent local seismic network and consequently the level of seismic activity and its spatial and temporal distribution were unknown. The PLUTONS Project deployed eight broadband seismic stations throughout the LVS between November 2011 and March 2013. This study shows event locations and types from November 2011 through March 2012. We analyze 591 seismic events within 20 km of Lastarria. Most events cluster tightly beneath Lastarria and almost no activity is observed beneath Cordón del Azufre or the primary inflation center. All events are reviewed manually, and located using a velocity model that assimilates prior studies and accounts for hypocenters within the edifice up to 5 km above sea level. More than 90% of the resulting hypocenters are shallower than 10 km below sea level. The waveforms have characteristics similar to those observed at many other volcanoes, suggesting five classes of events: volcano-tectonic (VT), long-period 1 (LP1), long period 2 (LP2), hybrid (HY), and unknown (X). Frequency-magnitude analysis reveals distinct b-values ranging from 1.2 for VT events to 2.5 for LP1 events. Based on the spatial distribution of events and the b-values, we infer that seismic activity is driven mainly by movement of fluids and gases associated with the regional magma zones and inflation centers. The seismic activity is energetic at times, and quieter at others, suggesting the presence of episodic magmatic and/or hydrothermal activity, focused at Lastarria. Our findings indicate that the previously observed inflation signals are indeed volcanic in origin. These results also demonstrate the potential for success of a future seismic monitoring system and provide a framework for interpreting the subsequent observations.